Regional income convergence and regional policy in the European Union - J. Andrés Faí\~naa; Jesús López-Rodríguez (European Regional Science Association (ERSA), 2004)
In this paper we use a generalized entropy index such as the Theil index to analyze regional inequalities in Europe. We proved that there is a synchronization between the convergence and catching-up process of objective 1 regions towards the EU15 average with the reform of the EU regional policy. During the period 1982-1988 the Theil index shows that inequalities between objective 1 regions and non-objective 1 regions have increased while from 1989 onwards the reduction in the inequalities between these two groups has been the norm. We also remark the fact that there are high disparate rates of growth among objective 1 regions both within countries and across countries but our computations show also a trend towards a more balanced growth among objective 1 regions within and across EU countries. This success of the European Union regional policy in objective 1 regions will mean a big opportunity for Central and Eastern European countries and hence the increases in competition arising from an enlarged European market combined with a suitable regional development policy should in the future boost the growth of those countries. In the last part of the paper we made a simulation for the funding envelope from 2007, based on the 2000-2006 budget. We show that the figures of the Agenda 2000 provide enough financial support for 90% of the total CEEC population and for 75% of “current” objective 1 population. Key Words: Regional Policy, European Enlargement, Central and Eastern European Countries, Strategic Planning, Regional Growth, Regional Development
Keywords: 330; Regional Policy; European Enlargement; Central and Eastern European Countries; Strategic Planning; Regional Growth; Regional Development